(untitled) (Caderno de Ciências Agrárias, 2016)
Rain is an active factor in erosion and the knowledge of its erosive potential is of great importance for planning soil conservation technologies, however there is still a lack of information regarding rainfall erosivity in the Brazil, principally in the region Northeast. Thus, the objective of this study was to determine and model the rainfall erosivity and associate it to recurrence intervals in the region of Teixeira de Freitas, in the extreme south of the state of Bahia. The rainfall erosivity was determined by the erosivity index in 30 minutes (EI30), considering the kinetic energy of rainfall and its maximum intensity in 30 minutes. Probability distributions were applied and the best fit was used for determining the erosivity return period. The average annual erosivity for the region was 3,722.0 MJ mm ha-1 h-1 yr-1 and the best fitting distribution was the Log-Normal 2P.